2020
DOI: 10.1001/jamainternmed.2020.1369
|View full text |Cite
|
Sign up to set email alerts
|

US Public Concerns About the COVID-19 Pandemic From Results of a Survey Given via Social Media

Abstract: had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
160
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(177 citation statements)
references
References 2 publications
13
160
0
4
Order By: Relevance
“…Social media platforms have proven to be very engaging with the public [8]. Data analysis of social media content has provided insight into political campaigns, media, healthcare, and daily events [9]. In this study, we retrieved and analyzed public data available on Twitter to investigate the rapid shift in telehealth adoption amidst the recent coronavirus Covid-19 pandemics.…”
Section: Discussionmentioning
confidence: 99%
“…Social media platforms have proven to be very engaging with the public [8]. Data analysis of social media content has provided insight into political campaigns, media, healthcare, and daily events [9]. In this study, we retrieved and analyzed public data available on Twitter to investigate the rapid shift in telehealth adoption amidst the recent coronavirus Covid-19 pandemics.…”
Section: Discussionmentioning
confidence: 99%
“…Our survey indicates that the majority of participants (88%) did not agree that the COVID-19 situation would be under control and defeated in the DRC. A possible explanation for this type of attitude could be the reports of rapid spreading of the disease and the high mortality figures in developed countries, like in Italy and in the United States of America [ 15 ]. However, another explanation given by respondents was that “it is hard to trust the Congolese health system since most political authorities usually travel overseas to seek for a better health care”.…”
Section: Discussionmentioning
confidence: 99%
“…A lthough the effects of the COVID-19 pandemic on the public's anxiety levels have been well documented by traditional media, the degree to which the pandemic affects physician stress and personal life has not yet been quantified in the United States. 1,2 Investigators reported a heavy psychological toll on health care workers in Wuhan and other regions of China. 3 Anticipating a surge in mental health care needs in U.S. health care workers, others have called for similar systematic assessments of frontline providers.…”
Section: Background and Importancementioning
confidence: 99%